Thermal Performance of Polymer-Modified Concrete for Sustainable Building Envelopes (Future Cities and Environment, 2024)
This study investigates the thermal performance of polymer-modified concrete composites, focusing on their potential to enhance energy efficiency in building envelopes. Four types of recycled polymers—low-density polyethylene (LDPE), highdensity polyethylene (HDPE), polypropylene (POLYP), and polyester—were integrated into concrete mixes at varying percentages (10%, 20%, and 30%). Key thermal metrics, including thermal transmittance (U-value), decrement factor (f), decrement delay (ϕ), admittance (Y), optimum thickness, and heat capacity per unit area, were measured using the admittance approach and a MATLAB program conforming to CIBSE standards. Results indicate that higher polymer content generally improves thermal damping and reduces cyclic transmittance. Notably, LDPE 30% exhibited the best performance, achieving a decrement factor of 0.179 and a time lag of 11.76 hours. HDPE 30% demonstrated a decrement factor of 0.206 and a time lag of 10.85 hours. Polyester 30% showed a decrement factor of 0.310 and a time lag of 8.50 hours. Sensitivity analysis revealed that optimal wall thicknesses for polymermodiffed concretes are lower than those required for conventional concrete, with LDPE 30% requiring an optimal wall thickness of 0.128 meters compared to 0.269 meters for conventional concrete. This research underscores the dual benefits of waste management and energy performance improvement, advocating for the practical application of polymer-modified concrete in sustainable construction. The study ranks the polymers’ efficiency as LDPE, HDPE, POLYP, and Polyester. These findings support the use of recycled polymers in concrete, promoting sustainability through effective waste management and improved thermal efficiency in building envelopes.